Declarations on euthanasia and assisted dying. Issue 9 (21st October 2017) - Inbadas, Hamilton; Zaman, Shahaduz; Whitelaw, Sandy; Clark, David
ABSTRACT: Declarations on end-of-life issues are advocacy interventions that seek to influence policy, raise awareness and call others to action. Despite increasing prominence, they have attracted little attention from researchers. This study tracks the emergence, content, and purpose of declarations concerned with assisted dying and euthanasia, in the global context. The authors identified 62 assisted dying/euthanasia declarations covering 1974–2016 and analyzed them for originating organization, geographic scope, format, and stated viewpoint on assisted dying/euthanasia. The declarations emerged from diverse organizational settings and became more frequent over time. Most opposed assisted dying/euthanasia.